The Impact of Broken Homes on Students’ Academic Performance - Leizl F Abrantes; Leomarich F Casinillo (Indonesian Journal Of Educational Research and Review, 2020)
This study aimed to analyze the influence of problems encountered from broken homes on academic performance among senior high students. This study adopted a Descriptive-Correlational design. A constructed survey questionnaires were given to 168 students identified through purposive sampling for the response of the problems encountered of being in a broken home.  Through simple random sampling, another 168 students from two-parent homes were used as a comparison. Secondary data such as grade point average was taken from the School Registrar. Descriptive statistics were employed to summarize the different variables and Spearman correlation was undertaken to identify the significant relationship between variables. Results revealed that there is no significant difference between the academic performance of students from single-parent homes and two-parent homes. It is also found out that problems encountered by students from single parent homes does not affects their studies and learning attitudes. With the aid of Spearman Rho Correlation Coefficient, it denotes a highly significant relationship between problems encountered by the students and their academic performance. This suggest that students are considering their problems as motivation to strive hard in their studies in order to become successful.